Clinical pathways and wait times for OSA care in Ontario, Canada: A population cohort study. Issue 2 (3rd April 2019) - Povitz, Marcus; Bray Jenkyn, Krista; Kendzerska, Tetyana; Allen, Britney; Pendharkar, Sachin R.; Ouedraogo, Alexandra; George, Charles F.P.; Shariff, Salimah Z.
Abstract: RATIONALE: Lengthy wait times for obstructive sleep apnea (OSA) in Canada remain a concern. OBJECTIVES: To describe the clinical pathway for OSA and determine wait times from assessment of OSA until continuous positive airway pressure (CPAP) treatment in Ontario. METHODS: We conducted a population-based cohort study from 2006 to 2013. We used billing information to identify clinic visits for sleep complaints and polysomnography (PSG). We calculated the time from primary care visits until diagnostic PSG (diagnostic time) and from PSG until CPAP initiation (treatment time) for each year. We used logistic regression to identify factors associated with diagnostic and treatment time >6 months. RESULTS: A total of 216 514 CPAP users were included. Most (52%) had a diagnostic PSG without a sleep assessment and 52% underwent a titration PSG. The median diagnostic wait for hospital and community-based facilities were 260 (IQR 87–869) days and 203 (36–838) days, respectively, with less than 50% of patients undergoing PSG within 6 months of PC assessment. The median treatment wait was 108 days (57–193) at hospital and 82 days (45–143) at community-based facilities; less than 70% started on CPAP within 6 months. Female sex, recent hospitalization and having diagnostic PSG at a hospital were associated with longer diagnostic and treatment times. CONCLUSIONS: The clinical pathway for assessment and treatment of OSA in Ontario is highly variable and current wait times in Ontario remain lengthy. Interventions to improve physician education, redistribute sleep medicine resources and adopting new technologies should be considered.